(untitled) - T R Bull (London, 1995)
This book provides an essential overview of the subject in five major sections: examination, ear, nose, pharynx and larynx, and head and neck. The focus is on examination and diagnosis, with brief details of medical and surgical treatment where appropriate. A wealth of high-quality photographs are used to depict both common and atypical disorders, and to illustrate the lastest developments in areas such as phonography, laser surgery, endoscopic nasal and sinus surgery, and imaging
Keywords: otolaryngologic diseases,otolaryngology, operative